Determinants profitability syariah construction listed companies in Malaysia / Che Wan Zuraiha Che Wan Abu Bakar - Che Wan Abu Bakar, Che Wan Zuraiha (2019)
This paper focus on studying the Determinants Profitability in Sharia Construction Listed Companies in Malaysia. The company chosen are Mitrajaya Holdings Bhd, Gamuda Bhd, Gadang Holdings Bhd, Mercury Industries Bhd, MGB Bhd, Muhibbah Engineering (M) Bhd, Kimlun Corporation Bhd, TRC Synergy Bhd, Protasco Bhd, Lebtech Bhd, Dkls Industries Bhd, Ekovest Bhd, Fajarbaru Builder Group Bhd, Melati Ehsan Holdings Bhd, Bina Puri Holdings Bhd, Crest Builder Holdings Bhd, George Kent (Malaysia) Bhd, Ho Hup Construction Company Bhd, Hock Lian Seng Holdings Ltd, UM Corporation Bhd, Ireka Corporation Bhd, JAKS Resources Bhd, MTD ACPI Engineering Bhd, Stella International Holdings Ltd, WCT Holdings Bhd. The objective of this study is to examine the determinants companies’ profitability using 4 independent variable which are liquidity, capital structure, gross domestic product, inflation rate and firm size and the dependent variable is profitability measure by ROA. Furthermore, the variables are used to measure the firm’s profitability as a whole for a period of 10 years from 2009 to 2018, in which brings the population sample to a total of 250 observations. The data used are based on the company’s annual report and are obtained from various sources such as the World Bank’s database and Thomson Reuters Eikon. Numerous methodologies were used such as Descriptive Statistics, Correlation Analysis, Pooled Least Square (POLS) Regression Analysis and Random Effect Model (REM) and Fixed Effect Model and Hausman Fixed in analyzing the dependent and independent variables. Results show that 3 variables are significant with firm’s profitability which are liquidity, capital structure and firm size. Liquidity and firm size show the results are positive significant with the dependent variable while capital structure is negative significant relationship. The other 2 variables are not significant which are inflation rate and gross domestic product.